Climate Change and Rivers - Paul Huttner and Phyllis Mauch Messenger (Open Rivers, 2016)

(untitled)
Open Rivers contacted Paul Huttner, Chief Meteorologist for Minnesota Public Radio. Huttner writes the Updraft blog and hosts MPR’s weekly Climate Cast. We wanted to learn more about the impact climate change is having on rivers and communities and how discussions about environmental issues and water are changing.